Palliative care in motor neurone disease: where are we now?. (January 2019) - Oliver, David J.
Palliative care has a very important role in the care of patients with motor neurone disease and their families. There is increasing emphasis on the multidisciplinary assessment and support of patients within guidelines, supported by research. This includes the telling of the diagnosis, the assessment and management of symptoms, consideration of interventions, such as gastrostomy and ventilatory support, and care at the end of life. The aim of palliative care is to enable patients, and their families, to maintain as good a quality of life as possible and helping to ensure a peaceful death.